Education Try out Model on Competency Test with Peplau Concept and Coaching Method toward of Passing Competency Test - Halimatussakdiah Diah (Jurnal Gema Keperawatan, 2017)
This research is aims to see the effect of Education Try out Model on competency test by applying the Peplau concept and coaching methods toward the nursing students of Diploma III on the opportunities of passing a competency test in Banda Aceh in 2016. This research is a Quasiexperiment study. The research was designed using cross sectional study by collectingthe data (survey) on students who have followed the Education Try out Model on competency test. This research was conducted in Banda Aceh on 1 to 10 September 2016. The sample consists of 50 students who are determined by consecutive sampling. Bivariate analysis t-test used to analyze the data. The results of study shows that there was a mean difference between the first measurement with the second measurement that was -0.780 where the standard deviation was 0.418 (p value 0.00).